Supporting rabies control in India. (24th September 2016) - Mansfield, Karen L.; Banyard, Ashley C.; Fooks, Anthony R.; Franka, Richard; Isloor, Shrikrishna; Rahman, Abdul
Abstract : Earlier this year, Tony Fooks and colleagues described how, under a laboratory twinning project run by the World Organisation for Animal Health (OIE), the UK's OIE Reference Laboratory for rabies, based at the APHA in Weybridge, had been working with the Changchun Veterinary Research Institute in the People's Republic of China to help the institute develop into an OIE Reference Laboratory itself ( VR, March 5, 2016, vol 178, pp 231‐232). Now, the APHA is taking part in a further three‐year project to build rabies diagnosis capability in Bangalore, India, as he and his colleagues explain below